Factors Motivating Muslims to Pay Zakat: A Narrative Review Based on the Scopus Database - Andriansyah, Yuli (Nuban Jagadhita Centre, 2024)
Purpose: This study aims to provide a comprehensive narrative review of these factors to identify the key motivators and barriers to zakat compliance. By synthesizing insights from global research, this study seeks to inform strategies for enhancing zakat systems, optimizing collection mechanisms, and maximizing socio-economic impact. Methodology: A narrative review methodology was employed, systematically analyzing relevant studies from the Scopus database. The thematic analysis focused on drivers such as religiosity, social norms, technological integration, institutional trust, knowledge, demographic contexts, and economic factors influencing zakat compliance. Findings: Findings highlight that religiosity is a primary motivator, supported by trust in institutions, social dynamics, and technological advancements that facilitate zakat payments. However, barriers such as insufficient awareness, governance challenges, and economic instability hinder compliance. Demographic and contextual variations further influence behavior, requiring tailored approaches. This study underscores the dual role of zakat as a spiritual and socio-economic tool. By addressing identified drivers and barriers, policymakers and zakat institutions can enhance compliance, foster social equity, and contribute to sustainable development. This research integrates diverse perspectives into a structured framework, advancing the understanding of zakat payment behaviors. It provides actionable insights for improving zakat systems globally and identifies areas for further exploration, such as the role of emerging financial paradigms and digital innovations.